y^2 - 12y + 36 = 9
subtract 9 from each side
y^2 - 12y + 27 = 0
easy factoring by inspection
(y - 3)(y - 9)
y = 3
y = 9
27 + 9 = 36
9+9+9+9 = 36
45
-3
9 divided by 9 equals 1, and 3 times 12 equals 36. 1 plus 36 equals 37.
3a + 9 =3X(a + 3)
If: -2.5x+4.5y = 9 and -x+1.5 = 9 Then: x = -36 and y = -18
4x = -36 x = -9
9 out of 36 equals 25%
x2 + 13x + 36 = 0 so (x+4)(x+9) = 0 so that x = -4 or x = -9
9 times what equals 36 = 324
-36 + 2w = -8w + w -36 + 2w = -7w -36 = -7w - 2w -36 = -9w w = -36/-9 = 4